Redesigning Language Learning Strategy Classifications - Ag. Bambang Setiyadi (TEFLIN, 2004)
In the current study a total of 79 university students of a 3-month English course participated. This study attempted to explore what learning strategies language Indonesian learners used and how the strategies were classified. To increase the internal consistency of the hypotesized scales, Cronbach Alpha coefficients of internal consistency were computed for each scale of skill-based areas, namely: speaking, listening, reading and writing. Correlation analysis was also conducted to see how variance of speaking, listening, reading and writing in language learning strategy questionnare were correlated. The result shows that each skill-based scale has realatively high reliability with alpha .73, .67, .69, .80 for listening, speaking, reading, and writing respectively. It is also found out that the four scales are significantly and positively correlated. The classification of learning strategies based on the language skills is a new way of learning strategy measurement, which may be worth considering in the Indonesian context in which English is learned as a foreign language.